Decision Support System For Selection Of Drug Supplier With Weighted Product Method - Sastra Wandi Nduru; Harmoko Lubis (Jurnal ICT : Information and Communication Technologies, 2022)
Supplier data is seen from historical orders to suppliers about company addresses, prices, variants of drugs owned and drug quality, and supported by the Weighted Product method to support the decision of which supplier to choose to be a priority. The result of this research is a program to rank and determine supplier selection at GrandMed Hospital. The decision support system for determining supplier selection using the Weigthed Product method at GranMed Hospital has been able to be built using UML and made with the Visual Basic 2008 programming language